Анатолій Пашкевич як явище в українській пісенній творчості - Андрійчук, П. (Народна творчість та етнографія, 2005)
This article commemorates the life and work of Anatoly Pashkevych – contemporary Ukrainian composer whose music became real folk art of our times. He died in the second day of Orthodox Christmas of 2005 but his music will never die in the souls of Ukrainian people. He was a great composer, chorus leader, poet, and jut a very modest men, whose entire life was sincerely devoted to songs a, poetry and music.